Excessive Postprandial Sleepiness in Two Young Adults Effectively Treated with Antidiabetic Medications - Ohara, Shinji; Takaki, Ryusuke; Sasaki, Shigeto (Sleep Science, 2024)
We herein describe the cases of two young Japanese adults who presented with excessive daytime sleepiness (EDS). Based on their history, the postprandial nature of the sleepiness was suspected, although the patients themselves were not aware of the association. Oral glucose tolerance tests (OGTTs) reproduced the sleepiness and showed the patterns of insulin resistance (IR) compatible with type-2 diabetes mellitus (T2DM) in one patient and glucose intolerance in the other. There was no evidence of chronic hyperglycemia in either patient. Antidiabetic medications resulted in the disappearance of EDS in both patients; in one, a repeat OGTT revealed improved IR. We suggest that postprandial somnolence can present with EDS, and it can be effectively treated with antidiabetic medications, and that the OGTT can be useful in identifying IR, which may be the underliyng cause of the excessive postprandial somnolence.
Keywords: postprandial period; disorder of excessive somnolence; oral glucose tolerance test; insulin resistance